Improving prairie relationships: utilizing the arts in elementary science education - Smith, Gabrielle (My University, 2025)
Due to budget and liability issues, teachers often find connecting students to hands-on learning opportunities and nature-specific lessons challenging to implement. This also means that children do not have as many opportunities to interact with nature in school and other settings as compared to the past. Children have also become less interested in pursuing science topics and careers past their K-12 schooling. Improving teacher access to lesson plan resources can create an easier way to incorporate nature education in the classroom. This study addresses this issue by creating a science-based lesson plan centered around prairies that incorporates arts-based activities. It includes a matrix of educational sites in Manhattan, Kansas, that support prairie education and other education topics for future research and build-out. This lesson plan includes an accessible field trip to the Marianna Kistler Beach Museum of Art, which uses art to support science education. An immersive field trip is encouraged but not required for the lesson to increase students’ hands-on, experiential learning opportunities. These outcomes incorporate science-based prairie education with artistic activities to fill an educational gap in prairie programming in Manhattan, Kansas. Furthermore, these resources have been incorporated into a website to be accessible to anyone who wishes to view or utilize them.
Keywords: Prairie; Elementary education; Science; Art